WE‐G‐500‐06: Offline PET/CT Imaging of Scanned Proton and Carbon Ion Beams: Initial Clinical Experience for Different Tumour Sites - Parodi, K.; Bauer, Julia; Kurz, Christopher; Unholtz, D.; Sommerer, F.; Frey, K.; Haberer, T.; Herfarth, K.; Welzel, T.; Combs, S.; Debus, J. (Medical Physics, 2013)
Purpose: To evaluate offline Positron Emission Tomography (PET) /Computed Tomography (CT) for in‐vivo verification of scanned proton and carbon ion irradiation of tumours in different anatomical locations. Methods: At our combined ion therapy facility, in‐vivo PET/CT‐based verification of beam delivery is being performed using a commercial scanner (Siemens Biograph mCT) installed just outside of the treatment rooms. More than 70 patients with tumours in different anatomical locations received at least one 30 min long post‐irradiation scan. PET measurements are compared to expectations using in‐house developed software tools based, among others, on the general purpose FLUKA Monte Carlo code. Results: Activation within the irradiated region could be visualised in all treatment sites, regardless of the ion species and applied dose level. For carbon ions, the most promising results could be obtained for irradiation of compact tumours in the head and neck and hypofractionated treatment of liver lesions with restricted motion. Here, range verification benefits from a marked delineation of the distal activated area, due to the dominant contribution of 11C projectile fragments. For abdominopelvic sites (prostate, sacral chordoma) the typical use of opposed fields, the extremely low counting statistics and the insufficient characterization of biological tissue parameters represent major challenges for range monitoring. Nevertheless, useful feedback on the correctness of the treatment delivery could be inferred in some convenient cases. For protons, the data confirmed the expected higher counting statistics and increased sensitivity to the knowledge of the tissue composition. The latter benefited from an improved tissue classification based on multimodal information in the brain region, while known limitations remain in the pelvic area (prostate). Conclusion: Offline PET/CT imaging of scanned ion treatment is feasible, but its clinical value strongly depends on the anatomical location and treatment strategy (ion species, dose level and multi‐field configuration). Parts of this work have been funded via the FP7 EU Project PARTNER (grant agreement 215840‐2), the BMBF Project DOT‐MOBI (grant agreement 01|B08002F), and the FP7 EU Project ENVISION (grant agreement 241851). © 2013, American Association of Physicists in Medicine. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08